Plastic surgeon’s obligation in UAE law between reality and expectations - Aisha Obaid Rashid ALqaydi, (Journal of Legal Sciences, 2024)
Cosmetic surgeries have increased recently, especially with the development of technology and the introduction of artificial intelligence to change human appearance without considering the risks and complications that may occur in the future. The main problem lies in the absence of a law or regulation that organazied the practice of this profession or specifying the responsibility of the plastic surgeon and the extent of his commitment to cosmetic surgeries. Especially the cosmetic ones, as reference is made to the rules of medical liability in the UAE issued in the year 2016 and its organizing regulations, or the UAE Civil Transactions Law, as this study came to clarify the position of the UAE law and judiciary on cosmetic surgeries while resorting in some places to the laws and comparative judiciary. This is done by explaining the nature of plastic surgery in the first section. The second section only dealt with the nature of the plastic surgeon’s obligation in the plastic surgery contract, and finally we present in the third section the plastic surgeon’s breach of his obligations, both morally and artistically, to arrive at several recommendations and results related to the research paper, including the necessity of establishing a law that regulates cosmetic surgeries of all kinds, and activating supervisory and judicial committees on private and governmental beauty centers in the United Arab Emirates.